Development of Helicoverpa armigera on different hybrids of sunflower (Helianthus annuus) - SHARMA, MONIKA; SINGH, GURDIP (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1999-2000 to study the development of Helicoverpa armigera (Hubner) on hybrids of sunflower (Helianthus annuus L.) at Ludhiana. Incubation period varied from 2.67 Â± 0.33 days on ’Jwalamukhi’ to 3.50 Â± 0.35 days on ’PSFH 67’. Less number of eggs hatched (87.34%), on ’PSFH’. The mean pupal survival was significantly higher on ’Jwalamukhi’, (87.82%) and ’MSF 8’ (82.64%) than on ’SH 3322’ (78.20%) and ’PSFH 67’ (72.72%). The mean pupal weight was maximum (282.75 Â± 10.00 mg) on ’Jwalamukhi’ and minimum (260.62 Â± 7.16 mg) on ’PSFH 67’. There were significant differences in female pupal length on all the 4 hybrids during March 1999. There were no significant differences in pre-oviposition, oviposition and post-oviposition period on 4 hybrids. Pre-oviposition period varied from 2.0 Â± 0.41 to 3.5 Â± 0.29 days. Oviposition period was maximum (3.75 Â± 0.26 days) on ’PSFH 67’ and minimum on ’MSFH 8’ (3.0 day) and ’SH 3322’ (3.0 Â± 0.58 days). Sex ratio was in the favour of males o)l’PSFH 67’. The number of eggs/laid female varied from 386.50 Â± 104.47 to 749.00 Â± 143.2, being maximum on ’Jwa1amukhi’ and minimum on ’PSFH 67’. The insect took less number of days (32.47 Â± 1.81 days) to complete its development on ’Jwalamukhi’ and more number of days (35.71 Â± 2.26 days) on ’PSFH 67’.